ANALISIS POTENSI PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN SIKKA TAHUN 2021-2022 (Studi kasus pada kantor Bapenda Sikka) - Stefanus Seferius Sareng; Yosefina Andia Dekrita; Yan Yanitza Salvanos (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This research aimed to determine the mapping of regional tax potential in Sikka Regency based on superior, potential, developing and underdeveloped sources. The research methods used in data collection are observation, documentation, interviews and literature studies. The data analysis technique used was a quantitative descriptive analysis technique using Klassen typology analysis. The findings of this research indicated that, out of the ten regional tax revenue sources in Sikka Regency, none, fall into Quadrant I (Superior Sources). This is because, among these ten sources, there is limited revenue potential and insufficient capacity to effectively manage high-potential sources. In Quadrant II (Developing Sources), no tax revenues were identified, as the government faces challenges with low-income potential and cannot efficiently manage even low-potential sources. Quadrant III (Potential Sources) includes street lighting tax, rural and urban land and building tax, and land and building acquisition tax (BPHTB). These sources are characterized by low potential, but the government has demonstrated a strong capacity to manage them effectively. Conversely, Quadrant IV (Underdeveloped Sources) comprises hotel tax, restaurant tax, entertainment tax, advertising tax, parking tax, groundwater tax, and non-metallic mineral and rock tax. These sources are constrained by both low-income potential and the government's limited ability to manage high-potential revenue streams effectively.